Analisis Klaim Konsep Ramah Lingkungan pada Bangunan Bandara SAMS Sepinggan Kalimantan Timur - Tunnisa, Sabrina Meisya; Winarto, Erwin Djuni (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2025)
The demand for air transportation continues to increase every year. To meet consumer demand, the Indonesian government is expanding the scale of airport development in Indonesia, especially in the East Kalimantan region. In the process of implementation, this development has a negative impact on the environment because the large use of energy in airports contributes to the occurrence of GHG emissions. In this case, the role of architecture is considered capable of minimizing negative environmental impacts by applying the concept of environmentally friendly architecture. The concept of environmentally friendly architecture considers the use of energy, maximization of sunlight, and utilization of water conservation in buildings. This study aims to assess the extent to which the application of green building aspects in the SAMS Sepinggan airport building. This research uses descriptive qualitative research methods with secondary data collection from relevant literature research, such as journals, web, and articles. Then, for each criterion, a suitability analysis was conducted using the Greenship standard for new buildings version 1.2. The results of this study indicate that Sultan aji Muhammad sepinggan Airport can already be considered as a green concept building. by obtaining an assessment of 35 points, which already meets the minimum points to get a bronze predicate as a building that applies the green building concept.